Sensor fusion (RFID) system for tabletop interaction - Ho, Choon Sing. (2009)
A feasibility study of how the RFID and multi-touch interaction can be used together to greatly enhance the gameplay experience of miniature war gaming is discussed here. The miniature war game used in this study was Battlelore, produced by Days of Wonder Inc. Battlelore is a turn-based, card-driven board game that is played on a hexagon grid board. The game rules of miniature war game are often complex and hard to grasp, especially for new players. Hence, this project aims to automate some of these complicated elements of miniature war gaming such as to roll the correct number of dice when the troops attack, to prompt error messages when players perform an illegal move and to provide information about the game in an intuitive way. Test was conducted to investigate whether RFID antennas placed on the capacitive sensing tile had any interference with each other. Results had shown that the metal ground plane used in the capacitive sensing tile caused the RFID signal to be detuned and the RFID reader was unable to retrieve information from a transponder placed within its reading range. Therefore, placing multiple RFID antennas across the surface of the capacitive sensing tile to detect positions of game objects is not possible. An alternative approach used was by scanning the game object on the RFID reader first before placing it onto a designated location on the capacitive sensing tile. In this way, the system will be able to know what type of object is being placed on it and the application will track the figurines’ position. As the user touches the game object and slide it across the surface, the system will check if the touch point is on any of the objects and updates the location automatically. This is possible if the game object is made of conductive materials and the surface area has to be large enough so that the capacitance from a person’s finger can be detected. Some other problems encountered were that the resolution of the capacitive sensing tile was not fine enough due to hardware limitation. There were only about 1 sensing point below each hexagon tiles. This cause the player to have a hard time trying to execute the task he/she wanted. However, given a finer sensing resolution, this setup would be a feasible approach.